Trends in HIV testing, the treatment cascade, and HIV incidence among men who have sex with men in Africa: a systematic review and meta-analysis - (:unkn) unknown (My University, 2023)
BackgroundGay, bisexual, and other men who have sex with men (MSM) are disproportionately affected by HIV. In Africa, MSM face structural barriers to HIV prevention and treatment that increase their vulnerability to HIV acquisition and transmission, and undermine the HIV response. In this systematic review, we aimed to explore progress towards increases in HIV testing, improving engagement in the HIV treatment cascade, and HIV incidence reductions among MSM in Africa.MethodsWe searched Embase, MEDLINE, Global Health, Scopus, and Web of Science for cross-sectional and longitudinal studies reporting HIV testing, knowledge of status, care, antiretroviral therapy (ART) use, viral suppression, and HIV incidence among MSM in Africa published between Jan 1, 1980, and March 3, 2023. We pooled surveys using Bayesian generalised linear mixed-effects models, used meta-regression to assess time trends, and compared HIV incidence estimates among MSM with those of all men.FindingsOf 9278 articles identified, we included 152 unique studies published in 2005–23. In 2020, we estimate that 73% (95% credible interval [CrI] 62–87) of MSM had ever tested for HIV. HIV testing in the past 12 months increased over time in central, western, eastern, and southern Africa (odds ratio per year [ORyear] 1·23, 95% CrI 1·01–1·51, n=46) and in 2020 an estimated 82% (70–91) had tested in the past 12 months, but only 51% (30–72) of MSM living with HIV knew their HIV status. Current ART use increased over time in central and western (ORyear 1·41, 1·08–1·93, n=9) and eastern and southern Africa (ORyear 1·37, 1·04–1·84, n=17). We estimated that, in 2020, 73% (47–88) of all MSM living with HIV in Africa were currently on ART. Nevertheless, we did not find strong evidence to suggest that viral suppression increased, with only 69% (38–89) of MSM living with HIV estimated to be virally suppressed in 2020. We found insufficient evidence of a decrease in HIV incidence
Keywords: African Research